Security prices in a competitive market : more about risk and return from common stocks - Brealey, Richard A. (Cambridge, Mass. : M.I.T. Press, 1971)
This book gives guidelines on Security prices in a competitive Market. It describe in non-technical language the behavior of common stock prices as revealed by formal statistical work. In the process they offer a broad survey of recent quantitative academic research on the subject, much of which is currently in an inaccessible form.
Includes index.
Includes bibliographical references: p. 219-230.
uaa 24/01/2019
Loans
Keywords: Stocks; Stock price forecasting